2015
DOI: 10.5194/gmd-8-3659-2015
|View full text |Cite
|
Sign up to set email alerts
|

A non-equilibrium model for soil heating and moisture transport during extreme surface heating: the soil (heat–moisture–vapor) HMV-Model Version 1

Abstract: Abstract. Increased use of prescribed fire by land managers and the increasing likelihood of wildfires due to climate change require an improved modeling capability of extreme heating of soils during fires. This issue is addressed here by developing and testing the soil (heat-moisture-vapor) HMVmodel, a 1-D (one-dimensional) non-equilibrium (liquidvapor phase change) model of soil evaporation that simulates the coupled simultaneous transport of heat, soil moisture, and water vapor. This model is intended for u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…This is because of the strong, near exponential variation of ρv*false(Tfalse) which plays a particularly important role for the Quincy sand case under surface fire conditions. This calls into question the results of Massman () who claimed that the nonequilibrium evaporation source term he used in his model, one version of which was based on Novak (), was critical to the improved performance of his simulations compared with Massman () and the original theory in Campbell et al (). The results herein suggest that the more likely source of the improvement was the inclusion of liquid flow which was neglected in both Campbell et al () and Massman ().…”
Section: Application Of the Improved Novak (2012) Model For Sementioning
confidence: 99%
See 1 more Smart Citation
“…This is because of the strong, near exponential variation of ρv*false(Tfalse) which plays a particularly important role for the Quincy sand case under surface fire conditions. This calls into question the results of Massman () who claimed that the nonequilibrium evaporation source term he used in his model, one version of which was based on Novak (), was critical to the improved performance of his simulations compared with Massman () and the original theory in Campbell et al (). The results herein suggest that the more likely source of the improvement was the inclusion of liquid flow which was neglected in both Campbell et al () and Massman ().…”
Section: Application Of the Improved Novak (2012) Model For Sementioning
confidence: 99%
“…Yamanaka et al () used a different sand but the same loam and clay soils in their numerical evaporation simulations based on PdV57. The Quincy sand was one of the soils used in the Campbell et al () surface fire experiments and numerical calculations and the Massman (, ) surface fire numerical simulations. The dependence of h v on T shown in the figure is solely due to the dependence of D v on T , which was given by D v ( T )=2.12×10 −5 ( T /273.15) 2 m 2 s −1 (Campbell, ).…”
Section: Application Of the Improved Novak (2012) Model For Sementioning
confidence: 99%
“…The f = 1 correction factor in Equation 8 accounts for the nonuniformity of the porous media, that is, represents smooth uniform spherical grains. Smits et al (2012) and Massman (2015) considered the film flow according to Equation 8 in their models and acknowledged the importance of considering the hydraulic conductivity due to the film flow for dry state conditions. But they found no improvement in the numerical results.…”
Section: Soil-water Retention Characteristicsmentioning
confidence: 99%
“…In addition, the experimental observation showed that the liquid‐gas interfacial area reaches its maximum value at a low saturation degree for sands (Costanza‐Robinson & Brusseau, 2002). Since there is limited research on predicting the interfacial area, a parabolic function proposed by Costanza‐Robinson and Brusseau (2002) and Massman (2015) is used in this study with a slight modification: alg=α1Sl1Slα2+α3Sl1Slα4. α 1 = 50, α 2 = 20, α 3 = 0.22, and α 4 = 0.25 are fitting parameters. Considering Equation and the fitting parameters, the interfacial area reaches its maximum value at S l = 1%.…”
Section: Theoretical Formulation Of Nonisothermal Multiphase Flowmentioning
confidence: 99%
See 1 more Smart Citation